Energy spectra in p-shell Λ hypernuclei and ^19_ΛF and spin-dependent Λ N interactions. (7th July 2019) - Kanada-En'yo, Yoshiko; Isaka, Masahiro; Motoba, Toshio
Abstract: Energy spectra of0s -orbitΛ states inp -shellΛ hypernuclei (^A_Λ Z ) and those in^19_ΛF are studied with the microscopic cluster model and antisymmetrized molecular dynamics using theG -matrix effectiveΛ N (Λ NG ) interactions. Spin-dependent terms of the ESC08a version of theΛ NG interactions are tested and phenomenologically tuned to reproduce observed energy spectra inp -shell^A_Λ Z . Spin-dependent contributions of theΛ N interactions to spin-doublet splitting and excitation energies are discussed. Energy spectra for unobserved excited states inp -shell^A_Λ Z and^19_ΛF are predicted with the modifiedΛ NG interactions.